2005
DOI: 10.3171/jns.2005.103.3.0473
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intracranial meningioma bleeding: clinicopathological features and outcome

Abstract: The mortality rate in preoperatively conscious patients (those in whom acute deterioration and irreversible brain damage were prevented by early diagnosis and definitive surgery) was similar (< 3% in the CT scanning era) to that documented in cases in which meningiomas did not bleed. In contrast, the associated morbidity rates were much higher. One-stage total removal of the hemorrhagic meningioma and hematoma is the treatment of choice in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
153
3
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(167 citation statements)
references
References 67 publications
8
153
3
3
Order By: Relevance
“…The previous study included intraventricular types of meningiomas, which showed a higher bleeding tendency, suggesting that an even lower risk of haemorrhage may be associated with the type of tumour described here (4,5). Convexity meningiomas showed the lowest risk for bleeding but generally presented with a subdural haematoma, in contrast to the present case.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The previous study included intraventricular types of meningiomas, which showed a higher bleeding tendency, suggesting that an even lower risk of haemorrhage may be associated with the type of tumour described here (4,5). Convexity meningiomas showed the lowest risk for bleeding but generally presented with a subdural haematoma, in contrast to the present case.…”
Section: Discussioncontrasting
confidence: 54%
“…In cases of tumour-associated haemorrhages, the clinical condition and outcome of the patient deteriorate due to the acute effects of the expansive process (4). Intratumoural and intracerebral haemorrhages associated with benign intracerebral tumours such as meningiomas are rare: only 68 cases have been described in the literature (4)(5)(6). No cases of neuroradiologically detected and clinically examined two-stage haemorrhages associated with meningiomas (WHO grade I) have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Meningiomas usually manifest as slowly progressive signs of neurological deficit, headache, or focal seizures, whereas apoplexy is rather uncommon. Meningioma associated with intracranial hemorrhage accounts for 1.3-2.4% of all meningiomas, 2) but cerebral infarction is a very rare clinical condition. We report a case of meningioma of the planum sphenoidale associated with cerebral infarction as a result of occlusion of the anterior cerebral artery (ACA) by the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…18) Pathologically, a malignant, angiomatous, and fibrous meningioma has a tendency to bleed. 3,12) In the present case, there were no findings to suggest the definitive source of SAH, but clot was identified on the tumor surface on MR images obtained 12 days after the onset, and fibrin deposit on the specimens obtained from tumor resection 19 days after resection. Review of the clinicopathological features of 145 meningiomas with spontaneous intracranial bleeding found that all 6 tumors arising in the posterior fossa caused SAH, and none of them presented with intratumoral hemorrhage.…”
Section: Sah In a Patient With A Meningioma And An Unruptured Aneurysmmentioning
confidence: 79%